Kajian Potensi Interaksi Obat pada Pasien COVID-19 di Rumah Sakit X Kota Samarinda: Study of Potential Drug Interactions in COVID-19 Patients at Hospital X Samarinda City - Shofia Siza Maulidia; Febrina Mahmudah; Yurika Sastyarina (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Coronavirus disease 2019 (COVID-19) is a respiratory infectious disease caused by a coronavirus known as SARS-CoV-2 and is currently a worldwide pandemic. Treatment management for COVID-19 patients is grouped based on the level of symptoms experienced by the patient. The use of large amounts of drugs (polypharmacy) in COVID-19 patients with moderate and severe symptoms can increase the possibility of drug interactions. This study aims to determine patient characteristics and the potential for drug interactions in COVID-19 patients at Hospital X Samarinda City. The data collection method was conducted retrospectively based on the medical records of COVID-19 patients hospitalized from March to December 2020. Data on potential drug interactions were analyzed using the Drugs.com application. The results showed that of the 30 patients with COVID-19, male-dominated (60%) and aged between 46 and 55 years (50%). Data on potential drug interactions showed that 28 out of 30 patients had the potential to experience drug interactions in the categories of severe (9,23%), moderate (74,62%), and mild (16,15%).